Preparation method of CaBTC / silicon dioxide composite aerogel and application of CaBTC / silicon dioxide composite aerogel in desulfurization

By in situ composite CaBTC in silica aerogel and introducing dopamine and silicone, a hydrophobic structure is formed, the selective adsorption performance of sulfur dioxide is improved, and the problem of insufficient adsorption capacity of silica aerogel in sulfur dioxide is solved, and the problem of insufficient adsorption capacity of silica aerogel is achieved. Highly efficient desulfurization effect and material stability.

CN119215859AActive Publication Date: 2024-12-31BENGBU COLLEGE

Patent Information

Application Number
CN202411487147.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-31
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The existing silica aerogels have limited capabilities in adsorption and removal of sulfur dioxide gas, which limits their application in the field of desulfurization materials, and lacks active groups on the surface, which affects the adsorption and capture efficiency.

Method used

CaBTC/silica composite aerogel is prepared by in-situ composite CaBTC in silica aerogel, sol-gel method and in-situ growth method are used to prepare CaBTC/silica composite aerogel, and dopamine and organosilane modifiers are introduced to form hydrophobic structures and activities to improve its selective adsorption performance on sulfur dioxide.

Benefits of technology

The efficient adsorption rate of sulfur dioxide gas is achieved to reach 96.2%, and the service life of the material is extended by improving structural stability and hydrophobic properties, which is suitable for the treatment of flue waste gas and sulfur-containing waste gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215859A_ABST
    Figure CN119215859A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite functional materials, in particular to a preparation method of CaBTC / silicon dioxide composite aerogel and application of the CaBTC / silicon dioxide composite aerogel in desulfurization, and the preparation method comprises the following steps: S1, preparing a 1, 3, 5-benzenetricarboxylic acid solution and a calcium acetate solution; s2, at the room temperature, tetraethoxysilane, an organosilane modifier and dopamine are sequentially added into a mixed solution of ethyl alcohol and water, hydrochloric acid is dropwise added to adjust the pH to 2.0-5.0, after hydrolysis reaction, ammonia water is dropwise added to adjust the pH to 9.0-10.5, and silicon dioxide hydrogel is obtained and further aged; s3, washing the aged silicon dioxide hydrogel with water to be neutral, gradually dropwise adding a 1, 3, 5-benzene tricarboxylic acid solution into the hydrogel, dropwise adding a calcium acetate solution after adsorption equilibrium, carrying out ultrasonic reaction for 10 minutes to 2 hours, washing, and freeze-drying, so as to obtain the product. A sol-gel method and an in-situ growth method are combined, CaBTC is loaded in a silicon dioxide gel structure for the first time to prepare CaBTC / silicon dioxide composite aerogel, and sulfur dioxide gas can be synergistically and efficiently removed through compounding of CaBTC and silicon dioxide aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite functional materials, and in particular to a preparation method of a CaBTC / silicon dioxide composite aerogel and application thereof in desulfurization. Background Art

[0002] With the development of industrialization, fossil fuels such as coal and oil have been mined and used in large quantities. During the combustion of fossil fuels, a large amount of SO x , causing serious pollution to the environment. Sulfur dioxide is one of the main pollutants in the atmosphere. When combined with rainwater in the sky, it will form acid rain. Therefore, the development of efficient desulfurization materials to reduce its emissions has become an urgent need in the field of environmental protection.

[0003] Silica aerogel is a lightweight, porous inorganic non-metallic material. Its structure is composed of a three-dimensional network, with a high porosity (80% to 99.8%), a pore size of 1 to 100 nm, and a rich micropore and mesoporous structure. These structural characteristics give silica aerogel a series of excellent physical properties, including low density, extremely large specific surface area, low thermal conductivity, etc., making silica aerogel widely used in the fields of thermal insulation, sound insulation, noise reduction, adsorption, etc. Although there are rich pore structures inside silica aerogel, there are no active groups on the surface of pure silica, and the adsorption and desorption capacity of sulfur dioxide gas is limited, which limits its application in the field of sulfur dioxide capture. At present, how to improve the adsorption capacity of silica aerogel porous materials for sulfur dioxide gas and give full play to the structural advantages of silica aerogel has become one of the hot issues in the field of desulfurization materials. For example, the invention patent with application number CN202210458940.X discloses a 2D lamellar structure silica-based desulfurization catalyst and a preparation method thereof. The 2D lamellar structure silica is used as a carrier, and an amino-containing compound is grafted on the 2D lamellar structure silica to obtain an amino-modified 2D lamellar structure silica. Then, a heteropoly acid is used as a catalyst active component, and the heteropoly acid molecules are anchored on the surface of the amino-modified 2D lamellar structure silica to obtain a heteropoly acid-supported amino-modified 2D lamellar structure silica catalyst, and its desulfurization rate in 30 minutes reaches more than 67.9%; for example, the invention patent with application number CN202410535956.5 discloses a solid desulfurizer and a preparation method thereof. The modified porous silica / alumina carrier is used to chelate Zn and Fe ions, and the desulfurizer prepared has a desulfurization rate of more than 99.8%.

[0004] CaBTC is a typical Ca-MOFs material with the characteristics of good stability, low toxicity, low price, relatively low density and good biocompatibility. Ca-MOFs has potential application value in gas adsorption, separation, drug delivery, electronics, magnetism and biomedicine. Since calcium-based materials have the ability to fix sulfur and MOFs materials and silica aerogels have good binding ability, the composite material obtained by in-situ compounding of CaBTC in silica aerogels helps to improve the desulfurization effect of silica aerogels. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a method for preparing a CaBTC / silica composite aerogel and its application in chemical adsorption desulfurization. On the one hand, a new composite material CaBTC / SiO2 composite aerogel is synthesized, and on the other hand, CaBTC and silica are composited to improve the selective adsorption of silica aerogel on SO2.

[0006] Based on the above purpose, the present invention provides a method for preparing a CaBTC / silicon dioxide composite aerogel, comprising the following steps:

[0007] S1: dissolving a certain amount of 1,3,5-benzenetricarboxylic acid in a mixed solution of ethanol and N,N-dimethylformamide, and dissolving by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0008] Dissolve calcium acetate monohydrate in deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0009] S2: at room temperature, tetraethyl orthosilicate, an organosilane modifier and dopamine are sequentially added to a mixed solution of ethanol and water, hydrochloric acid is added dropwise to adjust the pH to 2.0-5.0, and after a period of hydrolysis reaction, ammonia water is added dropwise to adjust the pH to 9.0-10.5 to obtain a silica hydrogel, which is further aged at a certain temperature;

[0010] By introducing an organic silane coupling agent, the different functional groups it possesses can adjust the surface hydrophilicity and hydrophobicity of the aerogel, and the hydrophilic silica aerogel can be transformed into a hydrophobic structure.

[0011] S3: After washing the aged silica hydrogel with water until it is neutral, 1,3,5-benzenetricarboxylic acid solution is gradually added dropwise to the hydrogel. After adsorption equilibrium, calcium acetate solution is added dropwise, and ultrasonic reaction is performed for 10 min-2 h. The obtained solid is washed and freeze-dried to obtain CaBTC / silica composite aerogel;

[0012] By dispersing calcium ions and organic ligand 1,3,5-benzenetricarboxylic acid in silica hydrogel, and then under the action of ultrasound, molecular self-assembly reaction can be quickly achieved and the CaBTC crystal structure can be formed in the silica gel network.

[0013] Preferably, in step S1, the usage ratio of 1,3,5-benzenetricarboxylic acid, ethanol, N,N-dimethylformamide, calcium acetate monohydrate, and deionized water is 1.0-2.0 mmol:4.0-6.0 mL:3.0-6.0 mL:1.0-2.5 mmol:4.0-8.0 mL.

[0014] Preferably, in steps S2-S3, the dosage ratio of the tetraethyl orthosilicate, the organosilane modifier, dopamine, ethanol, water, calcium acetate solution, and 1,3,5-benzenetricarboxylic acid solution is 0.7-1.5 mL: 0.05-0.25 mL: 0.3-0.5 g: 10-20 mL: 20 mL: 2-3.5 mL: 2-3.5 mL.

[0015] Preferably, in step S2, the organosilane modifier is one or more of methyltrioxymethylsilane, vinyltrioxyethylsilane, dimethyldiethoxysilane, ethynyltrimethoxysilane, and octadecyltrimethoxysilane.

[0016] Preferably, in step S2, the hydrolysis reaction time is 30-50 min.

[0017] Preferably, in step S2, the aging temperature is 35-60°C and the aging time is 1-2 days.

[0018] Preferably, in step S3, the freeze-drying time is 1-3 days.

[0019] The present invention further provides application of the CaBTC / silicon dioxide composite aerogel prepared by the preparation method in desulfurization.

[0020] Beneficial effects of the present invention:

[0021] The present invention combines the sol-gel method and the in-situ growth method to load CaBTC in the silica gel structure for the first time to prepare the CaBTC / silicon dioxide composite aerogel. The composite of CaBTC and the silica aerogel can synergistically and efficiently remove sulfur dioxide gas, and the adsorption rate of sulfur dioxide gas can reach 96.2%. At the same time, the introduction of organic silicon can improve the hydrophobicity of the composite aerogel, improve its waterproof performance, inhibit the water absorption and degeneration of the composite aerogel, and extend the service life. The composite material can be applied to the treatment of flue exhaust gas, sulfur-containing exhaust gas, etc.

[0022] Different from the traditional synthesis method of SiO2 gel, the present invention forms polydopamine / silica hydrogel by adding dopamine into the hydrolysis system. At the same time, the amino groups in the polydopamine can hydrogen bond with the hydroxyl groups in the silica hydrogel, so that the polydopamine runs through the hydrogel network structure. Furthermore, the hydroxyl groups and amino groups distributed in the hydrogel system undergo cross-linking reaction with the organic ligand 1,3,5-benzenetricarboxylic acid, thereby realizing the organic stable composite of silica and CaBTC materials, improving the structural stability of the target product CaBTC / SiO2 composite aerogel, and improving the mechanical strength of the composite aerogel to a certain extent. At the same time, the introduction of dopamine also helps to improve the selective adsorption performance of CaBTC / silica composite aerogel for sulfur dioxide. The reason may be that the silica modified by polydopamine makes the gel system contain a large number of active sites. Sulfur dioxide, as a strong Lewis acid, interacts with the amino Lewis basic groups in the aerogel, thereby greatly improving the selective capture performance of the composite aerogel for sulfur dioxide. In addition, the hydrogen atoms in the hydroxyl groups in the aerogel can form intermolecular hydrogen bonds with the oxygen atoms in the sulfur dioxide molecules, which also helps to improve the selective adsorption performance of the composite aerogel for sulfur dioxide.

[0023] The inventors also introduced organic silicon into the aerogel structure to improve its hydrophobicity, improve the waterproof performance of the composite aerogel, inhibit its water absorption and degeneration, and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a SEM scanning electron microscope image of the CaBTC / silicon dioxide composite aerogel prepared in Example 1 of the present invention;

[0026] Figure 2 The XRD spectrum of the CaBTC / silicon dioxide composite aerogel prepared in Example 2-3;

[0027] Figure 3 This is an infrared spectrum of the CaBTC / silicon dioxide composite aerogel prepared in Example 4;

[0028] Figure 4 It is a schematic diagram of a desulfurization system for adsorbing sulfur dioxide using a product prepared in an embodiment or a comparative example of the present invention;

[0029] Figure 5It is a desulfurization rate curve diagram of the products prepared in the embodiments or comparative examples of the present invention.

[0030] The markings in the figure are:

[0031] Figure 2 a is the XRD spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 2, Figure 2 b is the XRD spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 3, Figure 2 c is the standard XRD spectrum of CaBTC;

[0032] Figure 3 a is the standard infrared spectrum of CaBTC, Figure 3 b is the infrared spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 4. DETAILED DESCRIPTION

[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0034] The present invention provides a method for preparing a CaBTC / silicon dioxide composite aerogel according to an embodiment of the present invention, comprising the following steps:

[0035] S1: dissolving a certain amount of 1,3,5-benzenetricarboxylic acid in a mixed solution of ethanol and N,N-dimethylformamide, and dissolving by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0036] Dissolve calcium acetate monohydrate in deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0037] The dosage ratio of 1,3,5-benzenetricarboxylic acid, ethanol, N,N-dimethylformamide, calcium acetate monohydrate, and deionized water is 1.0-2.0 mmol: 4.0-6.0 mL: 3.0-6.0 mL: 1.0-2.5 mmol: 4.0-8.0 mL;

[0038] S2: at room temperature, tetraethyl orthosilicate, organosilane modifier and dopamine are sequentially added to a mixed solution of ethanol and water, hydrochloric acid is added dropwise to adjust the pH to 2.0-5.0, and after a hydrolysis reaction for 30-50 minutes, ammonia water is added dropwise to adjust the pH to 9.0-10.5 to obtain a silica hydrogel, which is further aged at 35-60°C for 1-2 days;

[0039] The organosilane modifier is one or more of methyltrioxymethylsilane, vinyltrioxyethylsilane, dimethyldiethoxysilane, ethynyltrimethoxysilane and octadecyltrimethoxysilane;

[0040] By introducing an organic silane coupling agent, the different functional groups it possesses can adjust the surface hydrophilicity and hydrophobicity of the aerogel, and the hydrophilic silica aerogel can be transformed into a hydrophobic structure.

[0041] S3: After washing the aged silica hydrogel with water until it is neutral, 1,3,5-benzenetricarboxylic acid solution is gradually added dropwise to the hydrogel. After adsorption equilibrium, calcium acetate solution is added dropwise, and ultrasonic reaction is performed for 10 min-2 h. The obtained solid is washed and freeze-dried for 1-2 days to obtain CaBTC / silica composite aerogel;

[0042] The dosage ratio of the tetraethyl orthosilicate, the organosilane modifier, dopamine, ethanol, water, the calcium acetate solution, and the 1,3,5-benzenetricarboxylic acid solution is 0.7-1.5 mL: 0.05-0.25 mL: 0.3-0.5 g: 10-20 mL: 20 mL: 2-3.5 mL: 2-3.5 mL;

[0043] By dispersing calcium ions and organic ligand 1,3,5-benzenetricarboxylic acid in silica hydrogel, and then under the action of ultrasound, molecular self-assembly reaction can be quickly achieved and the CaBTC crystal structure can be formed in the silica gel network.

[0044] The CaBTC / silicon dioxide composite aerogel prepared in this embodiment is used in desulfurization.

[0045] This embodiment combines the sol-gel method and the in-situ growth method to load CaBTC in the silica gel structure for the first time to prepare CaBTC / silicon dioxide composite aerogel. The composite of CaBTC and silica aerogel can synergistically and efficiently remove sulfur dioxide gas, and the adsorption rate of sulfur dioxide gas can reach 96.2%, which can be applied to the treatment of flue exhaust gas, sulfur-containing exhaust gas, etc.

[0046] Different from the traditional synthesis method of SiO2 gel, this embodiment forms polydopamine / silica hydrogel by adding dopamine to the hydrolysis system. At the same time, the amino groups in polydopamine can hydrogen bond with the hydroxyl groups in the silica hydrogel, so that the polydopamine runs through the hydrogel network structure. Furthermore, the hydroxyl groups and amino groups distributed in the hydrogel system undergo cross-linking reaction with the organic ligand 1,3,5-benzenetricarboxylic acid, thereby realizing the organic composite of silica and CaBTC materials, improving the structural stability of the target product CaBTC / SiO2 composite aerogel, and improving the mechanical strength of the composite aerogel to a certain extent. At the same time, the introduction of dopamine also helps to improve the selective adsorption performance of CaBTC / silica composite aerogel for sulfur dioxide. The reason may be that the silica modified by polydopamine makes the gel system contain a large number of active sites. Sulfur dioxide, as a strong Lewis acid, interacts with the amino Lewis basic groups in the aerogel, thereby greatly improving the selective capture performance of the composite aerogel for sulfur dioxide. In addition, the hydrogen atoms in the hydroxyl groups in the aerogel can form intermolecular hydrogen bonds with the oxygen atoms in the sulfur dioxide molecules, which also helps to improve the selective adsorption performance of the composite aerogel for sulfur dioxide.

[0047] The inventors also introduced organic silicon into the aerogel structure to improve its hydrophobicity, improve the waterproof performance of the composite aerogel, inhibit its water absorption and degeneration, and extend its service life.

[0048] Example 1 Preparation of CaBTC / silicon dioxide composite aerogel

[0049] S1: Dissolve 1.0 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 4.0 mL of ethanol and 4.0 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0050] Dissolve 1.5 mmol of calcium acetate monohydrate in 4.0 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0051] S2: 1.0 mL of tetraethyl orthosilicate, 0.35 mL of methyltrioxymethylsilane and 0.3 g of dopamine were dissolved in a mixed solution of 10 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 2.5. After the hydrolysis reaction lasted for 30 minutes, a certain amount of ammonia water was added to the system to adjust the pH value of the system to 9.0 to obtain silica hydrogel, which was further aged at 40°C for 1 day.

[0052] S3: The aged silica hydrogel was washed with water until it was neutral, and 2.0 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, 2.0 mL of calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 30 minutes. The obtained solid was washed alternately with ethanol and water for 3 times, and freeze-dried for 1 day to obtain CaBTC / silica composite aerogel.

[0053] Example 2 Preparation of CaBTC / silicon dioxide composite aerogel

[0054] S1: Dissolve 2.0 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 4.0 mL of ethanol and 6 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0055] Dissolve 1.5 mmol of calcium acetate monohydrate in 6 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0056] S2: 0.8 mL of tetraethyl orthosilicate, 0.35 mL of vinyl trioxyethyl silane and 0.3 g of dopamine were dissolved in a mixed solution of 15 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 3.5. After the hydrolysis reaction lasted for 30 min, a certain amount of ammonia water was added to the system to adjust the pH value of the system to 9.5 to obtain silica hydrogel, which was further aged at 35 °C for 2 d.

[0057] S3: The aged silica hydrogel was washed with water for 3 times, and 2.0 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, 2.0 mL of calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 40 min. The obtained solid was washed alternately with ethanol and water for 3 times, and freeze-dried for 3 days to obtain CaBTC / silica composite aerogel.

[0058] Example 3 Preparation of CaBTC / silicon dioxide composite aerogel

[0059] S1: Dissolve 1.5 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 6.0 mL of ethanol and 6.0 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0060] Dissolve 2.0 mmol of calcium acetate monohydrate in 8.0 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0061] S2: 1.0 mL of ethyl orthosilicate, 0.26 mL of dimethyldiethoxysilane and 0.4 g of dopamine were dissolved in a mixed solution of 15 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 3.5. After the hydrolysis reaction lasted for 30 min, a certain amount of ammonia water was added to the system to adjust the pH value of the system to 9.5 to obtain silica hydrogel, which was further aged at 60 °C for 2 d;

[0062] S3: The aged silica hydrogel was washed with water for 3 times, and 2.5 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, 2.5 mL of calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 50 min. The obtained solid was washed alternately with ethanol and water for 3 times, and freeze-dried for 1 day to obtain CaBTC / silica composite aerogel.

[0063] Example 4 Preparation of CaBTC / silicon dioxide composite aerogel

[0064] S1: Dissolve 1.5 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 5.0 mL of ethanol and 4.5 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0065] Dissolve 2.5 mmol of calcium acetate monohydrate in 6.0 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0066] S2: 0.7 mL of tetraethyl orthosilicate, 0.3 mL of ethynyltrimethoxysilane and 0.4 g of dopamine were dissolved in a mixed solution of 15 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 3.5. After the hydrolysis reaction lasted for 30 min, a certain amount of ammonia water was added to the system to adjust the pH value of the system to 10.0 to obtain silica hydrogel, which was further aged at 50 °C for 2 d;

[0067] S3: The aged silica hydrogel was washed with water for 3 times, and 3.5 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, 3.0 mL of calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 45 min. The obtained solid was washed alternately with ethanol and water for 3 times, and freeze-dried for 1 day to obtain CaBTC / silica composite aerogel.

[0068] Example 5 Preparation of CaBTC / silicon dioxide composite aerogel

[0069] S1: Dissolve 1.0 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 4.5 mL of ethanol and 3.0 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0070] Dissolve 1.5 mmol of calcium acetate monohydrate in 4.5 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0071] S2: 1.5 mL of tetraethyl orthosilicate, 0.45 mL of octadecyltrimethoxysilane and 0.5 g of dopamine were dissolved in a mixed solution of 20 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 3.0. After the hydrolysis reaction lasted for 50 min, a certain amount of ammonia water was added to the system, and the pH value of the system was adjusted to 10.0 to obtain silica hydrogel, which was further aged at 60 °C for 1 day;

[0072] S3: The aged silica hydrogel was washed with water for 3 times, and 3.5 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, 3.5 mL of calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 60 min. The obtained solid was washed alternately with ethanol and water for 3 times, and freeze-dried for 2 days to obtain CaBTC / silica composite aerogel.

[0073] Comparative Example 1 Preparation of CaBTC

[0074] S1: Dissolve 1.0 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 4.0 mL of ethanol and 4.0 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0075] Dissolve 1.5 mmol of calcium acetate monohydrate in 4.0 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0076] S2: 2.0 mL of calcium acetate solution was quickly added to 4.0 mL of 1,3,5-benzenetricarboxylic acid solution and ultrasonically reacted for 30 min to generate a white precipitate. After washing with ethanol and water alternately for 3 times, CaBTC was obtained.

[0077] Comparative Example 2 Preparation of organosilicon-modified silica aerogel

[0078] 1.0 mL of tetraethyl orthosilicate and 0.35 mL of methyltrioxymethylsilane were dissolved in a mixed solution of 10 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 2.5. After the hydrolysis reaction lasted for 30 minutes, a certain amount of ammonia water was added to the system, and the pH value of the system was adjusted to 9.0 to obtain silica hydrogel, which was further aged at 40°C for 1 day. The aged silica hydrogel was washed with water 3 times and freeze-dried for 1 day to obtain silicone-modified silica aerogel.

[0079] Comparative Example 3 Preparation of CaBTC / silicon dioxide composite aerogel

[0080] S1: Dissolve 1.0 mmol of 1,3,5-benzenetricarboxylic acid in a mixed solution of 4.0 mL of ethanol and 4.0 mL of N,N-dimethylformamide (DMF), and dissolve by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution;

[0081] Dissolve 1.5 mmol of calcium acetate monohydrate in 4.0 mL of deionized water and dissolve by ultrasonication to obtain a calcium acetate solution;

[0082] S2: 1.0 mL of tetraethyl orthosilicate and 0.35 mL of methyltrioxymethylsilane were dissolved in a mixed solution of 10 mL of ethanol and 20 mL of water at room temperature, and hydrochloric acid was added to adjust the pH value to 2.5. After the hydrolysis reaction lasted for 30 minutes, a certain amount of ammonia water was added to the system to adjust the pH value of the system to 9.0 to obtain silica hydrogel, which was further aged at 40°C for 1 day.

[0083] S3: The aged silica hydrogel was washed with water three times, and 2.0 mL of 1,3,5-benzenetricarboxylic acid solution was gradually added dropwise to the hydrogel. After adsorption equilibrium, calcium acetate solution was added dropwise to the system. The system was ultrasonically reacted for 30 minutes. The obtained solid was washed alternately with ethanol and water for three times, and freeze-dried for 1 day to obtain CaBTC / silica composite aerogel.

[0084] 1. Characterization of the structural properties of the products prepared in the examples:

[0085] Figure 1 This is a SEM scanning electron microscope image of the CaBTC / silicon dioxide composite aerogel prepared in Example 1: It can be seen from the figure that the silicon dioxide aerogel and the CaBTC are stably composited together, and there are abundant pores in the composite aerogel, which is conducive to the adsorption of sulfur dioxide gas.

[0086] Figure 2 This is the XRD spectrum of the CaBTC / silicon dioxide composite aerogel prepared in Example 2-3, wherein: Figure 2 a is the XRD spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 2, Figure 2 b is the XRD spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 3, Figure 2 c is the standard XRD spectrum of CaBTC. By comparison, it can be seen that the crystal structure of CaBTC remains unchanged in the silica aerogel, indicating that CaBTC can exist stably in the silica aerogel structure.

[0087] Figure 3 This is the infrared spectrum of the CaBTC / silicon dioxide composite aerogel prepared in Example 4, wherein: Figure 3 a is the standard infrared spectrum of CaBTC, Figure 3b is the infrared spectrum of the CaBTC / silicon dioxide composite aerogel obtained in Example 4. Figure 3 The characteristic peaks of CaBTC and silica can be observed in b, respectively, proving that the present invention successfully prepared the CaBTC / silicon dioxide composite aerogel.

[0088] 2. The products prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests, wherein the desulfurization efficiency test method was as follows:

[0089] like Figure 4 As shown, a mixer is used to mix 50% SO2 and 50% N2 by volume, and a flow meter is used to control the air intake. The gas adsorption system is a vertical stationary phase reactor, and the interior of the vertical furnace is a quartz wool insulation layer, and the center is a quartz tube reactor (d = 1.0 cm, the effective area is 10.0 cm). The reactor is plugged with quartz wool at the top and bottom. The desulfurization adsorption material prepared in the embodiment or comparative example is placed in the quartz tube reaction center area. The system is heated to 600 ° C, and the mixed gas is introduced from the bottom. After passing through the chemical adsorbent for 40 minutes, the gas discharged from the upper port enters the gas chromatograph to detect the SO2 concentration and determine the desulfurization rate. The remaining unreacted gas is treated with alkali solution. The desulfurization rate is calculated according to formula (I):

[0090]

[0091] The structural parameters and desulfurization rates of the product samples prepared in Examples 1-5 and Comparative Examples 1-3 are shown in Table 1. The specific test results are shown in Table 1. Figure 5 As shown:

[0092] Table 1

[0093]

[0094]

[0095] From Table 1 and Figure 5 It can be seen that the desulfurization rates of the CaBTC / silicon dioxide composite aerogels prepared in Examples 1-5 all reached more than 80%, but the desulfurization rates of different embodiments were also quite different, among which Example 2 had the highest desulfurization rate, reaching 96.2%, while Example 5 had the lowest desulfurization rate, which was 81.4%, but the specific surface area of ​​Example 5 was slightly higher than that of Example 2, indicating that the specific surface area is not the only factor affecting the desulfurization efficiency in the present invention, and another key factor affecting the desulfurization efficiency is the composite dosage ratio of CaBTC and silicon dioxide. Within a certain range, increasing the dosage ratio of CaBTC and silicon dioxide can improve the desulfurization efficiency. Therefore, the present invention can achieve a better desulfurization effect by reasonably adjusting the specific surface area of ​​the CaBTC / silicon dioxide composite aerogel and the composite dosage ratio of CaBTC and silicon dioxide.

[0096] At the same time, by comparing the test data of Example 1 and Comparative Example 3, it can be seen that the use of polydopamine to modify the silica aerogel helps to improve the desulfurization rate of the composite aerogel. At the same time, the desulfurization rate of Comparative Example 3 is higher than that of Comparative Example 1 and is much better than that of Comparative Example 2, indicating that the composite of CaBTC and silica aerogel can synergistically and efficiently remove sulfur dioxide gas and improve the desulfurization effect.

[0097] It can be seen from the experimental data of Examples 1-3 that the use of polydopamine-modified silica aerogel is helpful to improve the desulfurization rate of the composite aerogel, and CaBTC and polydopamine-modified silica aerogel can synergistically improve the desulfurization effect of the composite aerogel.

[0098] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention (including the claims) is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0099] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a CaBTC / silicon dioxide composite aerogel, characterized in that: The following steps are involved: S1: dissolving a certain amount of 1,3,5-benzenetricarboxylic acid in a mixed solution of ethanol and N,N-dimethylformamide, and dissolving by ultrasonication to obtain a 1,3,5-benzenetricarboxylic acid solution; Dissolve calcium acetate monohydrate in deionized water and dissolve by ultrasonication to obtain a calcium acetate solution; S2: at room temperature, tetraethyl orthosilicate, an organosilane modifier and dopamine are sequentially added to a mixed solution of ethanol and water, hydrochloric acid is added dropwise to adjust the pH to 2.0-5.0, and after a period of hydrolysis reaction, ammonia water is added dropwise to adjust the pH to 9.0-10.5 to obtain a silica hydrogel, which is further aged at a certain temperature; S3: After the aged silica hydrogel is washed with water until it is neutral, 1,3,5-benzenetricarboxylic acid solution is gradually added dropwise to the hydrogel. After adsorption equilibrium, calcium acetate solution is added dropwise and ultrasonically reacted for 10min-2h. The obtained solid is washed and freeze-dried to obtain CaBTC / silica composite aerogel.

2. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 1, characterized in that: In step S1, the usage ratio of 1,3,5-benzenetricarboxylic acid, ethanol, N,N-dimethylformamide, calcium acetate monohydrate, and deionized water is 1.0-2.0 mmol:4.0-6.0 mL:3.0-6.0 mL:1.0-2.5 mmol:4.0-8.0 mL.

3. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 1, characterized in that: In steps S2-S3, the dosage ratio of the tetraethyl orthosilicate, the organosilane modifier, dopamine, ethanol, water, the calcium acetate solution, and the 1,3,5-benzenetricarboxylic acid solution is 0.7-1.5 mL: 0.05-0.25 mL: 0.3-0.5 g: 10-20 mL: 20 mL: 2-3.5 mL: 2-3.5 mL.

4. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 3, characterized in that: In step S2, the organosilane modifier is one or more of methyltrioxymethylsilane, vinyltrioxyethylsilane, dimethyldiethoxysilane, ethynyltrimethoxysilane, and octadecyltrimethoxysilane.

5. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 1, characterized in that: In step S2, the hydrolysis reaction time is 30-50 min.

6. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 1, characterized in that: In step S2, the aging temperature is 35-60°C and the aging time is 1-2 days.

7. The method for preparing a CaBTC / silicon dioxide composite aerogel according to claim 1, characterized in that: In step S3, the freeze-drying time is 1-3 days.

8. Use of the CaBTC / silicon dioxide composite aerogel prepared according to the preparation method according to any one of claims 1 to 7 in desulfurization.

Citation Information

Patent Citations

  • Preparation method and application of metal-organic framework material Ca3(BTC)2

    CN109535433A

  • Preparation method and application of dopamine / silicon dioxide composite aerogel

    CN112452262A

  • MOFs / carbon aerogel adsorption filtering material and preparation method thereof

    CN112892489A

  • Process for producing particles comprising metal-organic framework compounds

    WO2012156436A1

Cited By

  • Aerogel composite material as well as preparation method and application thereof

    CN121016710A